Intelligent Policy Framework for Georouting Using Spatial Database - Saxena, Swasti; Amutha, B; Das, Abhinaba (International Journal of Engineering and Technology, 2018)
In todayâ€™s world of time effectiveness and climate change it is a necessity to take the right decision at the right time and act responsibly! Our carbon footprint is increasing day by day and our injudicious use of non-renewable sources of energy are posing a threat to get these energy sources exhausted soon! It is our responsibility to take an initiative towards it from our end.In this paper I am going to discuss about an Android Application which I have developed that will solve the problem of finding the shortest route from source to destination. This will lead to less wastage of car fuel and time to find the shortest path!This application has a two fold benefitÂ i.e. one of finding the shortest path from source and destination and second is acting as a world tour guide. It will not only show you the places of tourist attraction in that place but will also facilitate in providing suggestions for the cheapest means of transport that should be taken in order reach destination in minimum possible time and by spending minimum amount of money on travel!